CLINICAL CHARACTERISTICS OF POSTOPERATIVE SKIN SCARS IN PATIENTS WITH DIFFERENT CIRCADIAN RHYTHMS USING THE PLACENTA CRYOEXTRACT - Avetikov, D.S.; Toropov, O.A.; Lokes, K.P.; Voloshyna, L.V.; Steblovskiy, D.V.; Boyko, I.V.; Yatsenko, P.I. (World of Medicine and Biology, 2021)
Wound healing is a complex and dynamic process that depends on the coordinated activity of different types of epithelial cells, connective and vascular tissue. In previous studies in our department, the authors described that the healing of purulent wounds is significantly affected by the human chronotype, so patients with the morning type of chronotype tolerated surgery better than patients with the evening type, who were also operated on in the morning. Thus, the formation of a postoperative scar can be affected not only by the location of the wound, prolonged inflammatory process, as well as the time of surgery and the biological rhythm of the patient. From the data presented in the article we can conclude about our study, namely that the cryoextract of the placenta has a positive effect on wound healing not only in the early postoperative period, but also throughout the treatment period.
Keywords: biological rhythm; scar; scar prevention; crioextract; placenta